Remote Sensing Studies on Monitoring Natural Hazards Over Cultural Heritage Sites in Cyprus - Agapiou, Athos; Lysandrou, Vasiliki (My University, 2022)
This chapter presents examples of remote sensing studies for monitoring natural hazards related to ancient monuments and archaeological sites in Cyprus. Through these studies, the use of Earth Observation, and specifically the contribution of the European Copernicus Programme, is highlighted. Most of them have been carried out during the last years, within the framework of funded research projects. The various case studies presented in this chapter underscore Earth Observation’s mingling with other remote sensing techniques (both middle range and terrestrial) and geoinformatics towards inclusive monitoring of cultural heritage and prevention against possible hazards. The chapter unfolds in two parts: The first part introduces an overview of the potential contribution of Earth Observation to the Cultural Heritage Disaster Risk Management (DRM) cycle, with specific focus on the Eastern Mediterranean basin. The DRM includes six consecutive steps that require various inputs, including the context, threats and monitoring phases. For each step, the role of Earth Observation sensors and their related products are discussed. The second part of this chapter focuses on studies dealing with natural hazards in Cyprus using optical and radar datasets . These studies include the following: (a) soil erosion by water, (b) vegetation growth, and (c) detection of surface displacements , in sites with archaeological interest. The chapter ends with a comprehensive risk assessment report of various hazards (both natural and anthropogenic) using the Analytical Hierarchy Process (AHP) method. This assessment concerns the western part of Cyprus , namely the Paphos District, where more than 200 monuments are found.
Applications of Space Techniques on the Natural Hazards in the MENA Region